Berberine reduces fibronectin expression by suppressing the S1P-S1P2 receptor pathway in experimental diabetic nephropathy models. - Kaipeng Huang (Public Library of Science (PLoS), 2012)
The accumulation of glomerular extracellular matrix (ECM) is one of the critical pathological characteristics of diabetic renal fibrosis. Fibronectin (FN) is an important constituent of ECM. Our previous studies indicate that the activation of the sphingosine kinase 1 (SphK1)-sphingosine 1- phosphate (S1P) signaling pathway plays a key regulatory role in FN production in glomerular mesangial cells (GMCs) under diabetic condition. Among the five S1P receptors, the activation of S1P2 receptor is the most abundant. Berberine (BBR) treatment also effectively inhibits SphK1 activity and S1P production in the kidneys of diabetic models, thus improving renal injury. Based on these data, we further explored whether BBR could prevent FN production in GMCs under diabetic condition via the S1P2 receptor. Here, we showed that BBR significantly down-regulated the expression of S1P2 receptor in diabetic rat kidneys and GMCs exposed to high glucose (HG) and simultaneously inhibited S1P2 receptor-mediated FN overproduction. Further, BBR also obviously suppressed the activation of NF-κB induced by HG, which was accompanied by reduced S1P2 receptor and FN expression. Taken together, our findings suggest that BBR reduces FN expression by acting on the S1P2 receptor in the mesangium under diabetic condition. The role of BBR in S1P2 receptor expression regulation could closely associate with its inhibitory effect on NF-κB activation.